1988
DOI: 10.1002/ddr.430140307
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of denbufylline in patients with multi‐infarct dementia

Abstract: 14:195-198, 1988.The efficacy and tolerance of denbufylline (25 and 50 mg tid for three months) were investigated in 20 inpatients with cerebrovascular disease in a placebo-controlled, doubleblind parallel study. Denbufylline at 50 mg tid significantly improved the mental, emotional, and social capabilities of the patients; tolerance was acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Disturbances in the cAMPmediated signal transduction pathways of various neurotransmitters, such as noradrenaline (NA), serotonin (5HT), dopamine (DA) and HA, have been demonstrated in numerous neuropsychiatric and cardiovascular disorders (Cowburn et al, 1992;Feldman, 1993;Wachtel, 1990). Increasing cAMP levels through blocking of PDE4 enzymatic activity with PDE4 inhibitors such as rolipram (4-(3-cyclopentyloxy-4-methoxyphenyl-2-pyrrolidone) has been demonstrated to improve symptoms in a wide variety of disorders, including asthma (Torphy, 1998), chronic obstructive pulmonary disease (Sturton and Fitzgerald, 2002), atopic dermatitis (Hanifin et al, 1996), multiple sclerosis (Dinter et al, 1997), dementia (O'Connolly et al, 1988;Saletu et al, 1992), and depression (Wachtel, 1990). In cardiac studies, rolipram has been found to potentiate the action of inotropic agents and modulate cardiac contractility (Kajimoto et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in the cAMPmediated signal transduction pathways of various neurotransmitters, such as noradrenaline (NA), serotonin (5HT), dopamine (DA) and HA, have been demonstrated in numerous neuropsychiatric and cardiovascular disorders (Cowburn et al, 1992;Feldman, 1993;Wachtel, 1990). Increasing cAMP levels through blocking of PDE4 enzymatic activity with PDE4 inhibitors such as rolipram (4-(3-cyclopentyloxy-4-methoxyphenyl-2-pyrrolidone) has been demonstrated to improve symptoms in a wide variety of disorders, including asthma (Torphy, 1998), chronic obstructive pulmonary disease (Sturton and Fitzgerald, 2002), atopic dermatitis (Hanifin et al, 1996), multiple sclerosis (Dinter et al, 1997), dementia (O'Connolly et al, 1988;Saletu et al, 1992), and depression (Wachtel, 1990). In cardiac studies, rolipram has been found to potentiate the action of inotropic agents and modulate cardiac contractility (Kajimoto et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The PDE IV inhibitory potency was higher in the 9-alkyl substituents than in the 7-substituents and became weak with increases in the member of the condensed heterocycles. Then, the dihydroimidazole ring of compounds 1 which were highly potent, was converted to the imidazole (4) or triazole ring (5). Compounds 4 inhibited PDE IV activity more strongly than compounds 1, but also showed PDE I inhibitory activity, and so had lowered selectivity for PDE IV.…”
Section: Pharmacological Results and Discussionmentioning
confidence: 99%
“…PDEs have been classified into at least seven families, PDE I to PDE VII, and selective inhibitors of each isoenzyme have been developed as second-generation drugs. Among them, PDE IV inhibitors are now divided into three major families, phenylpyrrolidone derivatives, xanthine derivatives, and pyridopyrimidinedione derivatives, and they have been expected to have potent and selective effects on brain diseases, asthma, and inflammatory diseases. On the other hand, their central nervous system side effects, including emesis, limit their therapeutic potential. , The heart and central nervous system actions of xanthine PDE inhibitors may result from inhibition of other types of PDE than PDE IV and from adenosine antagonism. …”
Section: Introductionmentioning
confidence: 99%
“…2-(2-Hydroxyphenyl)-lH-imidazo[4,5-5]pyridine (15). An intimate mixture of salicylic acid (12.0 g, 87 mmol) and 2,3-diaminopyridine (10.0 g, 87 mmol) in polyphosphoric acid (230 g) was heated at 180 °C for 4 h. The reaction was cooled and added to ice/water, and the resulting solution was washed with CH2C12.…”
Section: -(2-(isobutyloxy)phenyl)-lh-imidazo[45-b]pyridine (Lg)mentioning
confidence: 99%